Indian agriculture and the multilateral trading system - Jha, Brajesh (New Delhi Book Well, 2001)
Indian agriculture and the multilateral trading system encompasses various contemporary issuses in Indian agriculture.Apart from this the book deals with the trade distortions prevalent in the world agriculture and the likely stance of India in the WTO Mi
Keywords: Agriculture-India; Agricultural development projects; Agriculture and state; International trade; Agricultural laws and legislation